VOLATILE CONSTITUENTS AND ANTIOXIDANT PROPERTY OF ESSENTIAL OIL FROM PLECTRANTHUS AMBOINICUS (LOUR) - A.MANJAMALAI,; DR. V.M. BERLIN GRACE, (International Journal of Pharma and Bio Sciences, 2012)
To investigate the in vivo and in vitro antioxidant activities of P. amboinicus essential oil having important volatile constituents such a Carvocrol, Thymol, Cis/Trans - Caryophyllene, and P-Cymene. Methods: For in vitro studies different concentration of essential oil ranging from 5 - 100µg/ml was used and the assay involves the DPPH free radical scavenging activity, Hydroxyl radical activity and reducing power activity. The in vivo study on antioxidant activity, was carried out in a lung cancer mice model induced by injecting 100µl of B16F-10 melanoma metastatic cell line suspension of about 1× 106 cells/ml in PBS into the tail-vein of C57BL/6 mice. The essential oil was given in the dose of 50µg/ml/dose for 21 days to each animal. The in vivo study involves the assay of the level of Catalase, Superoxide Dismutase, Glutathione Peroxidase, Lipid peroxidation, Nitric oxide and reduced glutathione. Finally, Lung was dissected out for histopathology study to confirm the lung metastasis. Results: The essential oil exhibited significant inhibition in DPPH free radical and hydroxyl radical formation. Similarly, it has got a significant reducing power towards such reactive molecules. In animal studies, the level of antioxidant enzyme activity were found to be normalized in the essential oil treated group for Catalase, Superoxide dismutase, glutathione peroxidase and Lipid peroxidation. Whereas, the toxic molecule nitric oxide level has been reduced upon essential oil treatment. The non-enzymatic antioxidant reduced glutathione was found to be increased, in the essential oil of P. amboinicus treated mice. The volatile compounds identified in GC – MS analysis in the essential oil were Carvocrol, Thymol, Cis – Caryophyllene, Trans – Caryophyllene, p- cymene as the major compounds with 96% comparison with the wilily and NBS library. Conclusion: The result obtained for both the in vitro and in vivo study shows that the essential oil of P. amboinicus has a significant antioxidant activity due to the presence of important bioactive compounds and hence, it can be subjected for pharmaceutical drug formulations.